A TALE OF TWO JIHADS: UNRAVELING THE ATROCITIES OF ISLAMIC STATE IN THE GREATER SAHARA (ISGS) AND JAMA’AT NASR AL-ISLAM WAL MUSLIMIN (JNIM) IN THE SAHEL - Afriyie, Frederick Appiah (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
The Sahel area of West Africa has become the latest battleground for Al-Qaeda affiliated Jama`at Nusrat Al-Islam wal-Muslimin (JNIM) and the Islamic State affiliated Islamic State in the Greater Sahel (ISGS). This piece as far as possible identifies the heightened atrocities perpetuated by both groups in the Sahel region. With little or no doubt, the strategies and ascendancy in atrocities orchestrated by the JNIM and ISGS could be largely hypothesized to have negative implications for Africa’s Sahel region (Chad, Mali, Niger and Mauritania). As a matter of concern, the paper confirms the said hypothesis and finds that the activities of the two Jihad-descent groups poses adverse security, social and political ramifications for the Sahel region and even beyond. With the theory of deprivation as the undergirding framework, the work explores how lack of basic needs and legitimate entitlements of citizens have catalyzed the dominance of JNIM and ISGS in the Sahel. Aside discussing the formation, trends of events, atrocities and strategies of JNIM and ISGS, the paper advances for a swift, action-oriented and collective efforts of governments within the Sahel region. In order to restore Sahel’s stability, increased security collaboration and strengthening the tenets of good governance are some worthwhile recommendations postulated.